REPRESENTATIONS OF THERAPY OF ANGINA IN CHILDREN AT THE INTERFACE OF SOCIAL AND BIOMEDICAL IN ZE - DIKPO TOLITON, TÉLESPHORE; MELIHO, C. Pierre (My University, 2019)
Medical anthropology has demedicalized the disease by integrating social practices around therapeutic logics in a broader context. Revisiting these social uses makes it possible to describe and analyze the therapeutic pathway of angina care between biomedical and social registers. This research focused on the observation of practices and the collection of stories of home care following episode of angina in children of the socio-cultural group Ayízɔ Sèdjè- Houègoudo in Zè in southern Benin. In total, forty actors selected by reasoned choice technique and route are approached namely: women and mothers of children, men specialized in angina, health professionals and representatives or leaders of local communities. The thematic analysis of care stories obtained through repeated interviews and ethnomedicine served as an approach to triangulation of corpora. The results address three aspects. First, the similarities and taxonomic singularities of popular and biomedical nosological entities around angina have been observed. Secondly, the results highlight the etiologico-therapeutic representations of angina in the patient and the caregiver. Thus, three categories of care providers among those observed state a plurality of representations, knowledge and practices of angina care in the community. Tertio, it results from the results a combination therapy of angina which circulates in synergy between the finger, the drug and the pharmacopoeia. As a result, there is a complementarity of medicines that strengthens self-therapy in the margins of medical discourse around self-medication
Keywords: domestic universe; self-medication; multiple therapy of angina; medical speech; Ayízɔ